Lectotypification of six names of species of Scabiosa s.l. (Caprifoliaceae) endemic to North Africa and related taxonomic notes - Barone, Giulio; El Mokni, Ridha; Di Gristina, Emilio; Domina, Gianniantonio (Phytotaxa, 2020)
As part of an ongoing project for the investigation of the Algerian-Tunisian flora, six names of species of Caprifoliaceae subfam. Dipsacaceae, endemic to central and western North Africa, described in the 19th and 20th Centuries under the genus Scabiosa, are here lectotypified. They are: Scabiosa camelorum Cosson & Durieu, Scabiosa cartenniana Pons & Quézel, Scabiosa daucoides Desf., Scabiosa farinosa Cosson, Scabiosa parielii Maire, and Scabiosa robertii Barratte. Taxonomic notes, distributisson and new unpublished data about plant phenology of these taxa are given.